Financial literacy and demographic factors on financial management: A study on MSMEs in Sleman Regency in the new normal era (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2022)
This study aims to determine the effect of financial literacy and demographic factors including gender, length of business, and operating revenues on the financial management of SMEs in Sleman Regency in the new normal era. The sample used is part of the total number of MSME actors in Sleman Regency. This study uses a survey method. The sampling technique used was accidental sampling. The data analysis technique used is multiple linear regression analysis. This study provides findings that financial literacy, gender, and length of business have a positive and significant effect on the financial management of MSMEs; and operating revenues has no significant effect on the financial management of MSMEs. The results of this study are expected to contribute and motivate SMEs in Sleman Regency by introducing financial service products. Thus, MSME actors can improve financial literacy and are able to manage finances properly and correctly, in order to maintain business continuity in this new normal era.Keywords: Financial Literacy, Demographic Factors, Financial Management, MSME